Utilization of Household Wasteas Liquid Organic Fertilizer on Shallot (Allium cepavar. ascalonicum (L.) Back). - ., Eliyani; Alvera Prihatini Dewi Nazari, Susylowati, (Universitas 17 Agustus 1945 Samarinda, 2018)
Utilization of household waste as organic fertilizeris an easy solution, cheap and effective because ithasvery largerole and benefits in terms of environment, sustainable agriculture/food security and socio-culture. The research consisted of two stages: the first was makingorganic liquid fertilizer (OLF) of household waste, followed by laboratory analysis to know OLF quality with reference tominimum technicalrequirements of OLF and compound biochemical fertilizer based on Minister of AgricultureRegulation No. 70/Permentan/SR.140/2011 and the second was OLFapplicationon shallot Tuk Tuk variety. The factorial experiment 2 x 3 was arranged in Randomized Complete Block Design with six times replication. The first factor wasthe OLF dose, consisted of two levels:500 and 1 000 mL polybag-1, while the second was OLFconcentration, consisted of three levels: 0, 50 and 100 mL L-1. Data were analized by Analysis of Variance.The results showed that the OLF contained nutrients quite complete (total N and micro nutrients), negative pathogenE. coli and Salmonella sp., very low metalscontent and higher number of fungi than minimum technical requiremnts ofOLF, although some parameters (total N, micro nutrients and number of bacteria) were lower. The effect of dose, consentration of OLF and the interaction were not significantly difference on variables observed.The quality of organic liquid fertilizerof household waste was sufficient to meet therequirements of Minister of Agriculture Regulation. A dose of 500 mL polybag-1witha concentration100 mL L-1tended to give abetter effect on the growth and yield of shallot bulb.